2021
DOI: 10.3389/fmed.2021.681388
|View full text |Cite
|
Sign up to set email alerts
|

A Five-Gene-Based Prognostic Signature for Hepatocellular Carcinoma

Abstract: Objective: This study intends to identify potential prognostic marker genes associated with the prognosis of patients suffering from hepatocellular carcinoma (HCC) based on TCGA and GEO analysis.Methods: TCGA-LIHC cohort was downloaded and the data related to HCC were extracted from The Cancer Genome Atlas (TCGA) database and subjected to differential analysis. HCC-related gene expression datasets were retrieved from the GEO database, followed by differential analysis. After intersection of the results of TCGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…In the case of our study, TOP2A was also considered as a key or core gene for the progression and development of HCC. This finding was coincided with previous studies 12,14,15,18,[20][21][22][23][24][25]27,[32][33][34][35][36]39,[41][42][43]45,46,48,50,51,[54][55][56][57][58]61 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the case of our study, TOP2A was also considered as a key or core gene for the progression and development of HCC. This finding was coincided with previous studies 12,14,15,18,[20][21][22][23][24][25]27,[32][33][34][35][36]39,[41][42][43]45,46,48,50,51,[54][55][56][57][58]61 .…”
Section: Discussionsupporting
confidence: 92%
“…Our findings also showed that CDC20 was a potential key biomarker that played an crucial or essential role for the development and progression of HCC. Different existing studies also supported our findings 10,13,14,17,18,20,24,30,32,37,40,41,44,48,50,[55][56][57] .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Compared to these gene signatures, our gene signature had the following features: first, our gene signature was established based on five GRGs that were independently associated with HCC prognosis. Considering the vital role of glycolysis in tumor development and progression, our gene signature is surely to have a better predictive performance than the previous predictive models [ 58 61 ]; second, some of the previous gene signatures lacked external validation using other datasets [ 60 ], consequently, we used the ICGC-LIRI—JP as an external validation cohort to verify the results of this study, which showed that the gene signature had good predictive performance.…”
Section: Discussionmentioning
confidence: 90%
“…3 C–D). We also compared our signature with 10 other established prognostic signatures, including the Zhao signature [ 27 ], Liu signature [ 28 ], Fu signature [ 29 ], Wang signature[ 30 ], Zhigang signature [ 31 ], Yang signature [ 32 ], Liang signature [ 33 ], Tang signature [ 34 ], Li signature [ 35 ], and Tian signature [ 36 ]. Interestingly, our TRPS had the highest C-index compared with these 10 established prognostic signatures, suggesting that our TRPS had a relatively better performance in predicting the prognosis of HCC than some of the other signatures (Fig.…”
Section: Resultsmentioning
confidence: 99%